2008
DOI: 10.1111/j.1365-2966.2008.13784.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Sunyaev-Zel'dovich effect from quasars

Abstract: Quasar feedback has most likely a substantial but only partially understood impact on the formation of structure in the universe. A potential direct probe of this feedback mechanism is the Sunyaev‐Zel'dovich (SZ) effect: energy emitted from quasar heats the surrounding intergalactic medium and induces a distortion in the microwave background radiation passing through the region. Here, we examine the formation of such hot quasar bubbles using a cosmological hydrodynamic simulation which includes a self‐consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 78 publications
5
52
0
Order By: Relevance
“…Thus only detailed simulations will be able to make precise predictions at the level needed to rule out or lend support to a particular model of AGN feedback. Although carrying out such simulations is beyond the scope of this paper, Equations (12) and (14) are roughly consistent with such sophisticated models (e.g., Thacker et al 2006;Chatterjee et al 2008), meaning that they can be used as an approximate guide to interpreting our results. Thus, we will use them to provide a general context for thinking about our observational results in terms of AGN feedback.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Thus only detailed simulations will be able to make precise predictions at the level needed to rule out or lend support to a particular model of AGN feedback. Although carrying out such simulations is beyond the scope of this paper, Equations (12) and (14) are roughly consistent with such sophisticated models (e.g., Thacker et al 2006;Chatterjee et al 2008), meaning that they can be used as an approximate guide to interpreting our results. Thus, we will use them to provide a general context for thinking about our observational results in terms of AGN feedback.…”
mentioning
confidence: 85%
“…If the gas is sufficiently heated, inverse Compton scattering will shift the CMB photons to higher energies. This thermal Sunyaev-Zel'dovich (tSZ) effect directly depends on the thermal energy of the free electrons that the CMB radiation passes through, and it has a unique spectral signature that makes it well suited to measuring the heating of gas and characterizing AGN feedback (Voit 1994;Natarajan & Sigurdsson 1997;Birkinshaw 1999;Platania et al 2002;Lapi et al 2003;Chatterjee & Kosowsky 2007;Chatterjee et al 2008;Scannapieco et al 2008;Battaglia et al 2010). On the other hand, if an object is moving along the line of sight with respect to the CMB rest frame, then the Doppler effect will lead to an observed distortion of the CMB spectrum, referred to as the kinetic Sunyaev-Zel'dovich effect.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several simulations on galaxy and group scales that have studied how "quasar" feedback impacts the total SZ decrement (Thacker et al 2006;Scannapieco et al 2008;Bhattacharya et al 2008;Chatterjee et al 2008). In this work, we explore whether AGN feedback incorporated into hydrodynamical simulations of structure formation can suppress the overcooling problem and resolve the current inconsistency between theoretical predictions and observations of the SZ power spectrum and X-ray pressure profile.…”
Section: Sz Power Templates and The Overcooling Problemmentioning
confidence: 99%
“…As a test of this quasar feedback interpretation, we investigate the dependence of our detected quasar tSZ signal on physical properties of the quasars, including M BH , L bol , and z. Because the cooling time of the shocked wind is long, the feedback energy E fb we measure is likely a total thermal feedback energy released into the surrounding gas over the quasar lifetime, and so a positive scaling of the tSZ signal with M BH and L bol is generically expected (Scannapieco & Oh 2004;Scannapieco et al 2008;Chatterjee et al 2008). We divide our quasar sample in two bins of M BH and L bol , and compare their tSZ Compton-y radial profiles in separate angular-scale stacked maps of each subsample.…”
Section: Separating Quasar Feedbackmentioning
confidence: 99%
“…Several analytical studies and simulations have suggested that the effects of quasar feedback on the host galaxy interstellar medium (ISM) and surrounding circumgalactic medium can be probed using the thermal Sunyaev-Zel'dovich effect (tSZ, Sunyaev & Zeldovich 1970, 1972 in the Cosmic Microwave Background (CMB) with the current generation of arcminute-scale angular resolution CMB experiments (Voit 1994;Natarajan & Sigurdsson 1999;Platania et al 2002;Lapi et al 2003;Chatterjee & Kosowsky 2007;Scannapieco et al 2008;Chatterjee et al 2008). Since the tSZ effect is a direct measurement of the total thermal energy in free electrons, a detection would provide a valuable probe of quasar feedback energetics.…”
Section: Introductionmentioning
confidence: 99%